COMPATIBILITY AND SYNERGISTIC EFFECTS OF INSECTICIDES WITH Metarhizium anisopliae FOR SUSTAINABLE MANAGEMENT OF Nephotettix virescens IN NORTH-EASTERN HIMALAYAS - Bimal Kumar Sahoo; Mahesh Pathak; Sandip Patra; Mohammad Abdul Waseem; Kennedy Ningthoujam; Pranab Dutta; Raghubir Kumar Patidar; Hia Kalita; Sikha Haritha; Ansh raj; Sushruta Boruah; Kasturi Sarmah; et al. (Journal of Animal and Plant Sciences, 2025)
Rice, a staple food crop cultivated globally, sustains the livelihoods of millions of people. However, its productivity is significantly compromised by the infestation of various insect pests including green leafhopper (Nephotettix virescens). The overreliance on chemical insecticides has resulted in the development of resistance in green leafhopper, increasing the challenges for its effective management. So, this study aims to investigate the integration of microbial agents with chemical insecticides as a sustainable approach for the management of N. virescens. Both individual and combined applications of the entomopathogen Metarhizium anisopliae and chemical insecticides against N. virescens under laboratory and field conditions were assessed. Initially, effects of six insecticides (Pymetrozyne, Deltamethrin, Thiamethoxam, Acephate, Imidacloprid and Diafenthiuron) on the vegetative growth of M. anisopliae were tested. Out of these, three insecticides (Imidacloprid, Pymetrozyne, and Thiamethoxam) were found to be compatible with the fungus, promoting increased vegetative growth, and were selected for further evaluation. Bioassay study against adults of N. virescens revealed that the LC50 and LC90 values for the combined treatments were lower than those for the insecticides alone, indicating synergistic effects, except for thiamethoxam. Pooled results revealed that the combination of M. anisopliae and imidacloprid proved to be effective against N. virescens, with 63.68% and 67.06% mortality in the first and second sprays, respectively, compared with 56.23% and 60.44% with imidacloprid alone under field condition. Scanning electron microscopy confirmed that the highest degree of conidial attachment occurred in the softer intersegmental regions near the legs, whereas fewer conidia were found in the head. These results suggest that M. anisopliae can be safely administered in the integrated pest management programme without hampering its efficacy for the management of rice leaf hoppers. Farmers and policymakers are encouraged to adopt integrated pest management strategies combining compatible microbial agents and insecticides to enhance sustainable management of green leafhoppers.
Keywords: Green leafhopper; Metarhizium anisopliae; compatibility; synergistic effect; scanning electron microscopy